(untitled) (Fiep Bulletin - online, 2013)
Amid conflicts and indefinite points concerning teaching contents in Physical Education, particularly from 6th to the 9th school year of the fundamental teaching, we realized sporty collective modalities hegemony. This happen from the whole Brazilian Physical Education historical process, mostly under the sporty institution influence in the middle of 1960 decade until middle of 1980 decade, this brought to the Physical Education legislation this trace in the fundamental teaching second segment. Further more, it configured the Physical Education as a mere to do for doing, depriving it, legally, of any knowledge systematizing attribution. We defend that Physical Education overcomes this hegemony, without these contents, and offers to students the opportunity of learning the Corporeal Culture knowledge, comprehending it conceptually, besides through corporeal experimentations, or be, in a critic-reflexive doing.